Pelatihan Pengambilan Keputusan bagi Siswa sebagai Calon Pemimpin Masa Depan di SMK Negeri 1 Tanjabtim - K.A. Rahman; Mohamad Muspawi; Avrilitzavivayarti Avrilitzavivayarti; Friscilla Wulan Tersta (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This decision-making training for students as potential future leaders was held at SMKN 1 Tanjabtim, Jambi Province, where the address is Jemantan, Muara Sabak Barat District, East Tanjung Jabung Regency, Jambi Province, 36561. The aim is for students to have strong motivation and self-confidence to lead yourself so that you can accept leadership responsibilities in a larger organization in the future and practice decision making as appropriate. The method consists of lectures, both small and large, then simulations, individual and classical approaches. In this mentoring, all participants will be trained to work both individually and in groups.